2004
DOI: 10.1353/cja.2004.0039
|View full text |Cite
|
Sign up to set email alerts
|

To Tell or Not to Tell? Professional and Lay Perspectives on the Disclosure of Personal Health Information in Community-Based Dementia Care

Abstract: Les développements en technologie informatique et la restructuration constante des services de santé en vue d'accroître les services en communauté plaident en faveur d'une amélioration des communications et l'échange d'information personnelle des patients entre les divers fournisseurs de soins sociaux et de la santé. Cependant, les principes de confidentialité et de protection de la vie privée sembleraient empêcher ces processus. Afin d'explorer les obligations pratiques, éthiques et légales qui relèvent des é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Privacy issues were relevant to our participants’ proposals; however, participants did not raise major privacy concerns. This corresponds largely with a study by Tracy et al . (2004) who found that patients, family carers and a range of professional practitioners involved in community‐based dementia care in Canada strongly supported interprofessional disclosure of personal health information.…”
Section: Discussionsupporting
confidence: 92%
“…Privacy issues were relevant to our participants’ proposals; however, participants did not raise major privacy concerns. This corresponds largely with a study by Tracy et al . (2004) who found that patients, family carers and a range of professional practitioners involved in community‐based dementia care in Canada strongly supported interprofessional disclosure of personal health information.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in a research study on the disclosure of personal health information in community-based dementia care, family caregivers valued being kept informed of the patient's condition even without the latter's consent. In contrast, professionals valued disclosure on the basis of its being in the patients' best interests (Tracy et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly important in relation to communication and the exchange of information about the care-recipient among health and social care providers and informal carers. On the one hand, research reveals that health professionals valued disclosure of information to both colleagues and informal carersjustified as being in the patients' best interests -even if disclosure came without the latter's consent (Tracy et al, 2004). Yet this is not without its problems.…”
Section: The Implementation Of Care Technologymentioning
confidence: 99%